2011
DOI: 10.1007/s11145-010-9294-3
|View full text |Cite
|
Sign up to set email alerts
|

Spelling performance of English consonants among students whose first language is Arabic

Abstract: The purpose of the present study was to examine the influence of some aspects of the Arabic phonological system on spelling English words. In Study 1, the spelling performance of Arabic students from grades four and six was compared with English students in cognate phoneme pairs which exist across both languages (/d/ and /t/), and pairs in which only one of the phonemes exists in Arabic (/b/ and /p/, /f/ and /v/) using a spelling test which contained words with the target phonemes. The findings showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Al-Harrasi (2012) refers to a concern in the matter of categorisation, because these categories do not account for why a student may have more than one kind of spelling mistake in a single word (e.g.,*discribtion = depiction) or why two students may make different sorts of blunder spelling the same word, (e.g., *permition, *permision, *permmission = authorization), so the categorisation of errors may be of limited help in the understanding of spelling errors. Allaith and Joshi's (2011) analysis suggested that Arabic students make mistakes using phonemes that doesn't exist in their own language; for instance, (/p/and/v/) so they substitute similar ones that do exist in Arabic for example, (/b/→/‫/ب‬and/f/→/‫. )/ف‬ They also examined students' ability to distinguish between/b/and/p/and between/f/and/v/.…”
Section: Ambiguous Errorsmentioning
confidence: 99%
“…Al-Harrasi (2012) refers to a concern in the matter of categorisation, because these categories do not account for why a student may have more than one kind of spelling mistake in a single word (e.g.,*discribtion = depiction) or why two students may make different sorts of blunder spelling the same word, (e.g., *permition, *permision, *permmission = authorization), so the categorisation of errors may be of limited help in the understanding of spelling errors. Allaith and Joshi's (2011) analysis suggested that Arabic students make mistakes using phonemes that doesn't exist in their own language; for instance, (/p/and/v/) so they substitute similar ones that do exist in Arabic for example, (/b/→/‫/ب‬and/f/→/‫. )/ف‬ They also examined students' ability to distinguish between/b/and/p/and between/f/and/v/.…”
Section: Ambiguous Errorsmentioning
confidence: 99%
“…In addition, Khan (2011) states that the difference in sentence patterns between a student's mother tongue and L2 leads them to commit many spelling errors such as silent letters. Also, it has been found that there is an impact of L1 phonology on English spelling for L2 learners (Allaith and Joshi, 2011). Abu-Rabia & Sammour (2013) asserted that "Successful English spelling performance involves the processes of segmenting the spoken word into its phonemic components and then selecting the appropriate graphemes to represent the phonemes".…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literacy is appraised not only by reading and writing accurately, but also spelling words correctly (Allaith and Joshi, 2011). Spelling mastery indicates the level of education while spelling errors reveal inaccuracy.…”
Section: Importance Of Spellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Since spelling mistakes may lead to problems in understanding the written script, the ability to spell constitutes an important part of the writing process (Khuwaileh & Al-Shoumali, 2000). According to Allaith & Joshi (2011), literacy is not evaluated only by the language users' reading and writing accuracy but also through correct word spelling. Al-Jarf (2010) also believes that mastery over spelling is a reflection of the level of education.…”
Section: Introductionmentioning
confidence: 99%